Inclusive Education: Key Success Factors in Educational Settings - Azis, Hendra Sidratul Azis (Balai Diklat Keagamaan Denpasar, 2025)
This article examines the significance of inclusive education in Indonesia, emphasizing the difficulties encountered by children with special needs. Based on information from the Central Statistics Agency (BPS) and UNICEF, around 650,000 children with disabilities exist in Indonesia, experiencing low rates of educational engagement. Inclusive education refers to a framework that offers all students, irrespective of any physical or mental disabilities, the chance to learn together in a shared setting. This study utilizes a library research approach to examine pertinent literature, focusing on educational models that can promote diversity in the classroom. Two fundamental bases for establishing inclusive education are philosophical and legal foundations, alongside three pertinent learning models: the Consultant Model, Teaming Model, and Collaborative Co-Teaching Model. The results suggest that introducing a personalized learning program (PPI) is essential for addressing the unique requirements of students. Suggestions are provided for schools and teachers to be ready to implement inclusive practices and engage parents in the educational process to foster an equitable and nurturing learning atmosphere for every student.